Generating single metalloprotein crystals in well-defined redox states: electrochemical control combined with infrared imaging of a NiFe hydrogenase crystal. Issue 43 (15th May 2017) - Ash, P. A.; Carr, S. B.; Reeve, H. A.; Skorupskaitė, A.; Rowbotham, J. S.; Shutt, R.; Frogley, M. D.; Evans, R. M.; Cinque, G.; Armstrong, F. A.; Vincent, K. A.
Abstract : We manipulate and verify the redox state of single metalloprotein crystals by combining electrochemical control with synchrotron infrared microspectroscopy. Abstract : We describe an approach to generating and verifying well-defined redox states in metalloprotein single crystals by combining electrochemical control with synchrotron infrared microspectroscopic imaging. For NiFe hydrogenase 1 from Escherichia coli we demonstrate fully reversible and uniform electrochemical reduction from the oxidised inactive to the fully reduced state, and temporally resolve steps during this reduction.